PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN KUIS INTERAKTIF MATERI GAYA KELAS IV SDN RONGGOMULYO 1 TUBAN - Romadhona, Siti Khovivah; Mizan, Saeful; Alex Rachman, Noor (Prodi PGSD Universitas PGRI Ronggolawe, 2025)
This study aimed to improve the science learning outcomes of fourth-grade students at SDN Ronggomulyo 1 Tuban through the implementation of the Problem-Based Learning (PBL) model integrated with interactive quizzes. This Classroom Action Research (CAR) was conducted in two cycles involving 28 students. Data were collected through learning outcome tests, observations, and documentation. The results showed a positive improvement in students' learning outcomes, with the number of students meeting the Minimum Mastery Criteria (KKM) increasing from 12 students (43%) in the pre-cycle to 15 students (54%) in the first cycle, and 24 students (86%) in the second cycle. Based on these findings, it is concluded that implementing the PBL model with interactive quizzes is effective in enhancing the science learning outcomes of fourth-grade students. This research contributes to the development of science learning practices in elementary schools by offering an innovative and proven-effective learning model to improve students’ understanding and achievement.